PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VII SMP NEGERI 2 GUNUNG TALANG KABUPATEN SOLOK - Lailatul Mutia Alda; Amril Amir (EDU RESEARCH, 2025)
This study has three objectives. The three objectives are as follows. First, to describe the news text writing skills of class VII students of SMP Negeri 2 Gunung Talang using the Think Talk Write Cooperative learning model. Second, to describe the news text writing skills of class VII students of SMP Negeri 2 Gunung Talang using the Discovery Learning learning model. Third, to analyze the effect of using the Think Talk Write Cooperative learning model on the News Text Writing Skills of Class VII Students of SMP Negeri 2 Gunung Talang. This type of research is quantitative with an experimental method. The research design uses a quasi-experimental type of posttest only control group design. The population used is class VII of SMP Negeri 2 Gunung Talang. The selected sample consists of two classes, namely class VII A as the experimental class and VII B as the control class. The research instrument used is a performance test. The analysis prerequisite test was carried out using the normality test and homogeneity test and t-test. There are three results of this study. First, the news text writing skills of class VII students of SMP Negeri 2 Gunung Talang using the Think Talk Write Cooperative learning model are in the good (B) qualification with an average value of 78.75. Second, the news text writing skills without using the Think Talk Write Cooperative learning model are in the Almost Sufficient (HC) qualification with an average value of 51.98. Third, based on the t-test, the hypothesis (H1) is accepted at a significance level of 95% because the t-test value> t-table (11.11> 1,67). Based on the results of the study, it can be concluded that the news text writing skills of class VII students of SMP Negeri 2 Gunung Talang using the Think Talk Write Cooperative learning model are better than using the Discovery Learning learning model (78.75> 51.98).